Antimicrobial Resistance Patterns of Urinary Escherichia coli Among Outpatients in Washington State, 2013–2017: Associations With Age and Sex. (26th March 2021) - Frisbie, Lauren; Weissman, Scott J; Kapoor, Hema; D'Angeli, Marisa; Salm, Ann; Radcliff, Jeff; Rabinowitz, Peter
Abstract: Background: Management of acute, uncomplicated cystitis in outpatients benefits from knowledge of drug resistance patterns in the population. However, antibiograms are often not available for the outpatient setting, and the role of host factors such as sex and age in assessing the likelihood of resistance are not well understood. We investigated whether antibiotic resistance patterns of outpatient urinary Escherichia coli isolates vary by age group and sex in a large database of antibiotic susceptibility test (AST) results from Washington State. Methods: We retrospectively analyzed AST data for outpatient urinary E. coli isolates in Washington State tested at a clinical reference laboratory from 2013 to 2017. In logistic regression models stratified by sex, we tested the associations of antibiotic resistance with patient age. Results: We found females >50 years had greater odds than females younger than 19 for resistance to amoxicillin-clavulanate (odds ratio [OR], 1.43; 95% confidence interval [CI], 1.22–1.69), ciprofloxacin (OR, 3.04; 95% CI, 2.48–3.74), ceftriaxone (OR, 2.58; 95% CI, 1.77–3.92), and gentamicin (OR, 1.62; 95% CI, 1.27–2.08) (all P < .001). Compared to males younger than 19, males >50 years had greater odds of resistance to ciprofloxacin (OR, 2.59; 95% CI, 1.18–5.69) and lower odds of resistance to amoxicillin-clavulanate (OR, 0.56; 95% CI, .34–.96) (all P < .05). Conclusions: These findings demonstrate that age and sex are associated with variability in antibiotic resistance patterns in the outpatient setting. Availability of outpatient antibiotic resistance data based on sex and age may be useful to inform empiric prescribing for outpatient UTIs and to support antibiotic stewardship efforts. Abstract : Availability of outpatient antibiotic resistance data based on sex and age may be useful to inform empiric prescribing for outpatient urinary tract infections and to support antibiotic stewardship efforts.